Completion Posterior Quadrant Disconnection After Failed Temporal Lobectomy: 2-Dimensional Operative Video. Issue 6 (25th August 2021) - Patel, Saarang; Markosian, Christopher; Dominguez, Jose F; Taha, Firas A; Tomycz, Luke D
Abstract: Epilepsy is a chronic seizure disorder that affects about 1% of the global population. 1 When seizure freedom cannot be obtained solely through antiseizure medicines (ASMs), the condition is termed medically refractory epilepsy (MRE). 2, 3 Though posterior quadrant disconnection (PQD) is underutilized in our experience, it is a highly effective surgical procedure for MRE restricted to the temporal, parietal, and/or occipital lobes. 4-12 In this operative video, we demonstrate a right-sided completion PQD following failed temporal lobectomy in an 8-yr-old female with focal MRE. We review technical nuances, including (1) extension/revision of prior scalp incision, (2) placement of subdural strip for the identification of phase reversal and central sulcus, (3) disconnection of parietal and occipital lobes, (4) extension of the corticectomy to the pia overlying the falcotentorial junction and into the prior temporal lobectomy defect, and (5) posterior disconnection of the corpus callosum. Postoperatively, the patient experienced subtle left-arm weakness and central fever, both of which resolved. An external ventricular drain (EVD) was placed in the ventricle/operative cavity and left for 3 to 4 d until the draining cerebrospinal fluid (CSF) cleared. As of 3-mo follow-up, she has been seizure-free without complications. In summary, PQD is a safe and effective treatment option for MRE that can be utilized not only as an initial operation but also after failed surgery. Appropriate patient consent was obtained to perform this procedure and present this clinical case and surgical video for academic purposes. Image at 4:00 licensed under CC BY-2.5, 2006, modified from http://upload.wikimedia.org/wikipedia/commons/7/70/Lateral_head_skull.jpg (flipped and rotated). Image at 4:42, Public Domain: Gray H. Anatomy of the Human Body. 1918. Bartleby.com, https://commons.wikimedia.org/wiki/File:Lobes_of_the_brain_NL.svg ; flipped, modified. Image at 6:42, Public Domain: House EL, Pansky B. A Functional Approach to Neuroanatomy. 1960. McGraw-Hill Book Company; https://upload.wikimedia.wikipedia.commons/5/52/Lawrence_1960_2.3.png ; modified.